Belimbing Tourism Village: A Green Marketing Strategy - Ni Wayan Sintya Dewi; I Ketut Sutama; Ni Gst Nym Suci Murni (Catuspata Press, 2021)
Abstract : Purpose: This study aims to determine the green marketing strategy in making a tourism business based on environment and health in Belimbing Tourism Village, Tabanan, Bali, Indonesia. Research methods: This is a mixed method research. SWOT (strengths, weaknesses, opportunities, threats) matrix is used to describe clearly how the external opportunities and threats faced by Belimbing Tourism Village can be adjusted due to its strengths and weaknesses. Findings: The strategies implemented in Belimbing Tourism Village are the use of social media and holidays as promotional materials, and green marketing as a concept in promoting to protect the environment, socio-culture and society. Implications: The strategies applied in Belimbing Tourism Village include social media and holidays as promotional materials, and green marketing as a concept in promoting to protect the environment and the socio-cultural things.